Can floseal™ be applied safely during otologic surgery? Assessment of ototoxicity in a chinchilla animal model - Carol Nhan; Aren Bezdjian; Abdullah Alarfaj; Sam J. Daniel (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background In otologic surgery good visualization is paramount, and patients with bleeding diatheses or who need to be anti-coagulated can present a significant challenge. Here, we determine whether Floseal™, a hemostatic matrix, is ototoxic in a validated animal model. Methods Nine chinchillas housed in the animal care facilities of the Montreal Children’s Hospital Research Institute were used for the study. After a myringotomy incision was made in each tympanic membrane, baseline auditory brainstem response measurements were performed at 8, 20, and 25 kHz. In each animal one ear was randomized to receive Floseal™ to the middle ear cavity, whereas the other ear served as the control and received 0.9% sodium chloride. Outcome measures included early (day 7) and late (day 30) auditory brainstem response, clinical evidence of facial nerve or vestibular disturbance and histological evidence of ototoxity. Results There was no significant hearing threshold shift on auditory brainstem response across all tested frequencies for both experimental and control ear. No animals receiving Floseal™ developed facial or vestibular nerve dysfunction and there was no histological evidence of ototoxicity. Conclusion Based on the preliminary ototoxicity assessment on nine chinchillas, transtympanic Floseal™ does not appear to be ototoxic. More studies are warranted to assess the safety and applicability of the product in humans.